A New Way for Beta Cell Neogenesis: Transdifferentiation from Alpha Cells Induced by Glucagon-Like Peptide 1. (13th March 2019) - Zhang, Zhen; Hu, Yinghui; Xu, Ningning; Zhou, Wenjun; Yang, Lei; Chen, Rongping; Yang, Rui; Sun, Jia; Chen, Hong
Abstract : Recent studies showed that alpha cells, especially immature cells and proalpha cells, might be the precursors of beta cells. Exposure to glucagon-like peptide 1 (GLP1) can ameliorate hyperglycemia in diabetic mice and restore the beta cell mass. In the present study, we adopted single high-dose (60 mg/kg, i.p.) streptozotocin (STZ) to model diabetes mellitus (DM) and randomly assigned short-tail (SD) rats to a normal group, a diabetic group, GLP1 groups (50  μ g/kg, 100  μ g/kg, and 200  μ g/kg), a GLP1 (200  μ g/kg) with exendin (9-39) group, and a GLP1 with LY294002 group. We found that the pancreatic insulin-glucagon-positive cell populations increased according to the increase in GLP1 exposure. By contrast, no insulin-amylase-positive cell populations or insulin/pan-cytokeratin cells were observed in the pancreatic sections. The GLP1 receptor antagonist exendin (9-39) and the phosphatidylinositol-4, 5-bisphosphate 3-kinase (PI3K) family inhibitor LY294002 not only suppressed protein kinase B ( Akt ), pancreatic and duodenal homeobox 1 ( Pdx1 ), forkhead box O 1 ( FoxO1 ), and mast cell function-associated antigen A ( MafA ) mRNA expression but also increased MAFB expression. We concluded that treatment with GLP1 might result in beta cell neogenesis by promoting the transdifferentiation of alpha cells but not by pancreatic acinar cells, ductal cells, or the self-replication of beta cells. The regulation on the GLP1 receptor and its downstream transcription factor PI3K/AKT/FOXO1 pathway, which causes increased pancreatic and duodenal homeobox 1 ( Pdx1 ) and MafA mRNA expression but causes decreased MAFB expression, may be the mechanism involved in this process.